2022
DOI: 10.3390/ani12223211
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Fruit from Nitraria tangutorum Improved Immunity and Abundance of Beneficial Ruminal Bacteria in Hu Sheep

Abstract: The fruit of Nitraria tangutorum (FNT) is reputed to possess medicinal properties; however, its effect on sheep (Ovis aries) is unknown. The aim of this study was to fill this gap. In a 3 × 3 Latin square design, six 12-month-old rumen-fistulated Hu rams (56.2 ± 8.26 kg; mean ± SD) were penned individually and offered one of three levels of FNT, namely, 0 g/d (control; CON), 16 g/d (N16), and 48 g/d (N48). The concentration of serum immunoglobulin G increased linearly (p = 0.03) with an increasing intake of FN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
1
2
0
Order By: Relevance
“…Meanwhile, these bacterium abundances were positively correlated with butyric acid, isovaleric acid, and valeric acid. Similarly, a previous study showed that feeding Hu sheep with the polyphenol-rich fruit Nitraria tangutorum could increase the abundance of Rikenellaceae_RC9_gut_group and Christensenellaceae_R-7_group [51]. In this study, a positive correlation was identified between Rikenellaceae_RC9_gut_group and butyric acid content.…”
Section: Effect Of Dfpe On Bacteria Communities In Vitrosupporting
confidence: 81%
“…Meanwhile, these bacterium abundances were positively correlated with butyric acid, isovaleric acid, and valeric acid. Similarly, a previous study showed that feeding Hu sheep with the polyphenol-rich fruit Nitraria tangutorum could increase the abundance of Rikenellaceae_RC9_gut_group and Christensenellaceae_R-7_group [51]. In this study, a positive correlation was identified between Rikenellaceae_RC9_gut_group and butyric acid content.…”
Section: Effect Of Dfpe On Bacteria Communities In Vitrosupporting
confidence: 81%
“…Lachnospira comprises many pectin degradation bacteria and has been shown to be enriched in the rumen of grass-fed steers [ 48 , 49 ]. Lachnoclostridium consists of many beneficial bacteria [ 50 ]. However, an increase in the relative abundances of Lachnospira and Lachnoclostridium was insufficient to alter ruminal fermentation in LADG calves.…”
Section: Discussionmentioning
confidence: 99%
“…The present research resulted in a non-significant increase in TGC and CHOL concentrations and a significant decrease in BHB in goats' blood, which points out the fact that feeding mixtures of the experimental groups were enriched with GSC ether extract (Table 1). Specifically, it is known that grape seeds have higher polysaccharide content, which can lower serum BHB concentrations and also inhibit the mobilization of adipose tissue and liver glycogen in the GSC10 group [48]. The amount of NEFA in the serum indicates how fat is metabolized, and the goats from the GSC groups' consistent concentration might be connected to the absence of alterations in CHOL.…”
Section: Discussionmentioning
confidence: 99%